The Singapore Lion : A Biography of S. Rajaratnam - Ng, Irene (Book collections on Project MUSE., 2010)
"Irene Ng has written a book that gives a comprehensive portrayal of Mr Rajaratnam - one of Singapore's outstanding leaders who played a crucial part in the momentous and crisis-ridden transition to iindependence. This is a book about the man and his wisdom. One would fail to appreciate him until one reads this absorbing book and reflects on the acuity and breadth of his insights and his wisdom."--S.R. Nathan, President of Singapore"In the course of a 33-year career in diplomacy, I met man ...